2021
DOI: 10.1097/gox.0000000000004058
|View full text |Cite
|
Sign up to set email alerts
|

Total Costs of Applying to Integrated Plastic Surgery: Geographic Considerations, Projections, and Future Implications

Abstract: Background: In 2020, the American Council of Academic Plastic Surgeons and the Association of American Medical Colleges recommended residency programs suspend away rotations and in-person interviews. This study quantifies applicant costs and potential savings in the residency application process resulting from that change, while also evaluating differences in cost with respect to geographic region of the applicant. Methods: A retrospective evaluation of the 2019–2020 Texas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“… 31 Additionally, Gordon et al reported a similar number of roughly $4000 on away rotation costs for applicants in the 2019–2020 application cycle. 32 Despite these known expenditures, over 90% of applicants report that the away rotations made them more competitive, and PDs agree that strong performance can make a candidate more competitive. Further, 27% of matched PGY-1 positions in the 2014–2015 application cycle were composed of away rotators, further strengthening this point.…”
Section: Away Rotationsmentioning
confidence: 99%
“… 31 Additionally, Gordon et al reported a similar number of roughly $4000 on away rotation costs for applicants in the 2019–2020 application cycle. 32 Despite these known expenditures, over 90% of applicants report that the away rotations made them more competitive, and PDs agree that strong performance can make a candidate more competitive. Further, 27% of matched PGY-1 positions in the 2014–2015 application cycle were composed of away rotators, further strengthening this point.…”
Section: Away Rotationsmentioning
confidence: 99%
“…Multiple studies have highlighted the high costs associated with applying to surgical subspecialties. 2 , 14 , 27 - 30 Our study demonstrates significant cost savings for surgical subspecialty applicants during the COVID-19 pandemic, which appears to be driven by a lack of away rotations and interview-related travel. Our findings show that even though there were savings associated with the 2021 application cycle, surgical subspecialty applicants still reported higher costs than their general surgical and nonsurgical peers.…”
Section: Discussionmentioning
confidence: 79%
“…The high cost of applications has been investigated extensively. In multiple recent studies in the literature, authors independently came to the same conclusion: there are exorbitantly high costs associated with applying to PRS residency, with applicants spending on average $9,000–$17,000, 10–12 compared to $4000–$6000 for the average medical school graduate. 13,14 Eliminating the costs of travel, lodging, and dining by performing only virtual interviews would theoretically lower this cost.…”
Section: Introductionmentioning
confidence: 93%